UPAYA PENINGKATAN HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK MELALUI PENDEKATAN BERMAIN - Winarno Winarno; Agus Margono; Deddy Whinata Kardiyanto (PHEDHERAL, 2018)
The purpose of this research is to improve learning outcomes in the long jump squat style class VII B SMP Negeri 8 Surakarta in academic year 2017/2018.This study is a classroom action research conducted in two cycles, and each cycle consists of 2 meetings. Research subjects of students of class VII B, amounting to 32 students. The data source comes from students, teachers, andresearchers. Data collection techniques use tests and observations. Data validityis by using data triangulation technique. Data analysis used qualitative descriptive analysis technique using percentage technique.The results of data analysis showed an increase learning outcomes long jump squat style as follows. The percentage of completeness in the pre-cycles is 31.25%or 10 students, unfinished 68.75% or 22 students. The percentage of completeness in the first cycle is 46.88% or 15 students, untargets 53.12% or 17 students. While on the percentage of completeness in the second cycle is 81.25% or 26 students, untargets 18.75% or 6 students. Learning outcomes long jump squat style has reached a target attainment of 80%.Based on the analysis above it can be concluded; that the application of the method of approach play can improve learning outcomes in the long jump squat style class VII B SMP Negeri 8 Surakarta in academic year 2017/2018.